The natural rate of interest II: Empirical overview - Dmitry Chervyakov; Philipp Johann König (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
The concept of the natural rate of interest (NRI) dates back to Wicksell (1898) and has since then been highly debated in the economic literature. In practice, estimates of the NRI can be employed as a versatile tool for macroeconomic analysis and are a core element within the popular neo-Wicksellian (or New-Keynesian) framework. The real rate gap, i.e. the difference between the actual interest rate and the NRI, provides valuable information about the state of the economy and can help policy makers to adjust the monetary policy stance. However, the NRI cannot be directly observed and has to be calculated from other economic data. While the empirical literature provides various estimation approaches, all of them are subject to serious measurement problems and yield fairly uncertain estimates. This Roundup reviews the advantages and shortcomings of the most popular measurement methods and presents an estimation of the NRI and the real rate gap based on the Laubach and Williams (2003) model.
Keywords: 330